Lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic, preparation method thereof and piezoelectric device
By preparing lead niobium indium niobium manganate-lead zirconium titanate piezoelectric ceramics, the problem of thermal runaway in traditional ceramics at high power and high temperature is solved, and high power performance and temperature stability are achieved to adapt to different temperature environments. .
Patent Information
- Application Number
- CN202411198644.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Traditional piezoelectric ceramics are prone to thermal runaway in high power and high temperature environments, making it difficult to take into account high power performance and temperature stability.
The chemical general formula xPb(In1/2Nb1/2)O3-0.05Pb(Mn1/3Nb2/3)O3-(0.95-x)Pb( Zr0.48Ti0.52)O3 is prepared by presintering, granulation, glue removal and sintering, and combined with adhesive and polarization treatment to form a piezoelectric ceramic with high voltage electrical constant and mechanical quality factor.
Maintain stable piezoelectric performance under high power and high temperature conditions, avoid thermal runaway, and have a wide operating temperature range, which improves application flexibility and applicability.
Smart Images

Figure CN119241235A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric ceramics, and in particular to a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic, a preparation method thereof, and a piezoelectric device. Background Art
[0002] The research background of high-power piezoelectric ceramics stems from the recognition of the needs and challenges of piezoelectric materials in high-power applications. The piezoelectric effect is a phenomenon in which a material deforms or generates charge distribution when stimulated by an external electric field, which makes piezoelectric materials have broad application potential in sensors, actuators, and energy conversion. At present, the common high-power output commercial piezoelectric ceramics on the market are mainly PZT series represented by PZT-8. However, in high-power applications, traditional piezoelectric materials are prone to thermal runaway under high power, resulting in performance degradation or even destruction. For this reason, there is an urgent need for a piezoelectric ceramic that can take into account both high-power performance and temperature stability. Summary of the invention
[0003] Based on this, it is necessary to provide a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic and a preparation method and a piezoelectric device thereof in order to address the problem of how to balance high power performance and temperature stability.
[0004] A lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic, wherein the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic has a general chemical formula of: xPb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -(0.95-x)Pb(Zr 0.48 Ti 0.52 ) 3 , wherein 0.01≤x≤0.05, x is the molar ratio.
[0005] After experimental verification, the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramics of the technical solution of the present invention can take into account both high-power performance and temperature stability. On the one hand, it can show good performance under high-power conditions; on the other hand, it can maintain stable piezoelectric performance under high-temperature conditions, and is not prone to thermal runaway problems when facing high-power and high-temperature environments, and can maintain good performance and reliability; in addition, it also has a wide operating temperature range, can adapt to different temperature environments, and can still maintain stable performance in application scenarios with large temperature changes, improving the flexibility and applicability of applications.
[0006] In a feasible implementation, the chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is: xPb(In1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -(0.95-x)Pb(Zr 0.48 Ti 0.52 ) 3 , where x is 0.01, 0.02, 0.03, 0.04 or 0.05.
[0007] A method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramics comprises the following steps:
[0008] Based on the chemical formula xPb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -(0.95-x)Pb(Zr 0.48 Ti 0.52 ) 3 The stoichiometric ratio of PbO powder and TiO 2 Powder, ZrO 2 Powder, MnO 2 Powder, In 2 O 3 Powder and Nb 2 O 5 The powders are mixed evenly, dried and pre-sintered to obtain pre-sintered powders after sufficient reaction;
[0009] Granulating the pre-calcined powder, and then pressing and molding to obtain a ceramic green sheet; and
[0010] The ceramic green sheet is subjected to a debinding process and a sintering process to obtain a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic.
[0011] The preparation method of the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramics of the technical solution of the present invention is simple in process. After experimental verification, the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramics prepared by the above preparation method can take into account both high-power performance and temperature stability. On the one hand, it can show good performance under high-power conditions; on the other hand, it can maintain stable piezoelectric performance under high-temperature conditions, and is not prone to thermal runaway problems in the face of high-power and high-temperature environments, and can maintain good performance and reliability; in addition, it also has a wide operating temperature range, can adapt to different temperature environments, and can still maintain stable performance in the face of application scenarios with large temperature changes, thereby improving the flexibility and applicability of the application.
[0012] In a feasible implementation, the temperature of the pre-sintering treatment is 800° C. to 900° C., the time of the pre-sintering treatment is 2 h to 3 h, and the heating rate of the pre-sintering treatment is 5° C. / min to 8° C. / min.
[0013] In a feasible implementation, before the calcined powder is granulated, the following steps are also included:
[0014] The pre-calcined powder is ball-milled at a rotation speed of 250 r / min to 300 r / min for 16 h to 20 h.
[0015] In a feasible implementation, the granulation operation is: mixing the pre-burned powder and the binder evenly, and then passing through a 100-mesh sieve; wherein the mass percentage of the binder is 5% to 7%.
[0016] In a feasible implementation, the temperature of the debinding treatment is 600° C. to 700° C., the heat preservation time of the debinding treatment is 5 h to 6 h, and the heating rate is 1° C. / min to 3° C. / min.
[0017] In a feasible implementation, the temperature of the sintering treatment is 1150° C. to 1200° C., the holding time of the sintering treatment is 2 h to 3 h, and the heating rate is 5° C. / min to 8° C. / min.
[0018] In a feasible implementation, the process further includes silver coating and polarization steps.
[0019] A piezoelectric device comprises the above-mentioned lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic or the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic prepared by any of the above-mentioned methods for preparing the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic.
[0020] The piezoelectric device of the technical solution of the present invention includes the above-mentioned lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic. After experimental verification, the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic of the technical solution of the present invention can take into account both high-power performance and temperature stability. On the one hand, it can show good performance under high-power conditions; on the other hand, it can maintain stable piezoelectric performance under high-temperature conditions, and is not prone to thermal runaway problems when facing high-power and high-temperature environments, and can maintain good performance and reliability; in addition, it also has a wide operating temperature range, can adapt to different temperature environments, and can still maintain stable performance in the face of application scenarios with large temperature changes, thereby improving the flexibility and applicability of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1A flow chart of a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to one embodiment of the present invention;
[0022] Figure 2 hysteresis loops of the embodiments of the present invention and the comparative examples;
[0023] Figure 3 The dielectric temperature spectra of the embodiments of the present invention and the comparative example are shown in FIG. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] The chemical formula of lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic (PIN-PMN-PZT) according to one embodiment is: 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -(0.95-x)Pb(Zr 0.48 Ti 0.52 ) 3 , wherein 0.01≤x≤0.05, x is the molar ratio.
[0027] The piezoelectric ceramics of this embodiment have a high piezoelectric constant (400pC / N) and a mechanical quality factor (1400) while also having a high Curie temperature (>300°C). The performance and temperature stability are higher than those of commercial hard ceramics, which well solves the problem of high performance and temperature stability of hard piezoelectric ceramics.
[0028] On the basis of the above-mentioned implementation mode, the chemical formula of lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is: xPb(In 1 / 2 Nb 1 / 2 ) 3-0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -(0.95-x)Pb(Zr 0.48 Ti 0.52 ) 3 , where x is 0.01, 0.02, 0.03, 0.04 or 0.05. When x is 0.01, the chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.01Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.94Pb(Zr 0.48 Ti 0.52 ) 3 When x is 0.02, the chemical formula of lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.02Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.93Pb(Zr 0.48 Ti 0.52 ) 3 When x is 0.03, the chemical formula of lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.03Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.92Pb(Zr 0.48 Ti 0.52 ) 3 When x is 0.04, the chemical formula of lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.04Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.91Pb(Zr 0.48 Ti 0.52 ) 3 When x is 0.05, the chemical formula of lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.05Pb(In 1 / 2 Nb 1 / 2 ) 3-0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.90Pb(Zr 0.48 Ti 0.52 ) 3 These new materials are able to maintain high Curie temperatures while maintaining high performance and can adapt to different operating temperatures.
[0029] After experimental verification, the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramics of the technical solution of the present invention can take into account both high-power performance and temperature stability. On the one hand, it can show good performance under high-power conditions; on the other hand, it can maintain stable piezoelectric performance under high-temperature conditions, and is not prone to thermal runaway problems when facing high-power and high-temperature environments, and can maintain good performance and reliability; in addition, it also has a wide operating temperature range, can adapt to different temperature environments, and can still maintain stable performance in application scenarios with large temperature changes, improving the flexibility and applicability of applications.
[0030] See also Figure 1 A method for preparing a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to an embodiment of the present invention comprises the following steps:
[0031] S10, based on the chemical formula xPb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -(0.95-x)Pb(Zr 0.48 Ti 0.52 ) 3 The stoichiometric ratio of PbO powder and TiO 2 Powder, ZrO 2 Powder, MnO 2 Powder, In 2 O 3 Powder and Nb 2 O 5 The powders are mixed evenly, dried, and then pre-sintered to obtain pre-sintered powders after sufficient reaction.
[0032] In step S10, high-purity oxides from Aladdin are used as raw materials, and the purity of each raw material is >99.8% to avoid the generation of impurities.
[0033] The operation of mixing the raw materials uniformly is as follows: using anhydrous ethanol as the ball milling medium, ball milling for 12 hours to 15 hours on a planetary ball mill (speed of 250 r / min to 300 r / min) to fully crush and mix the raw materials. The mixed slurry is dried in an oven.
[0034] In a feasible implementation, the operation of the pre-sintering treatment is: put the ground powder into a metal mold with a diameter of 30 mm and press it into a block with a press, the temperature of the pre-sintering treatment is 800℃~900℃, the time of the pre-sintering treatment is 2h~3h, and the heating rate of the pre-sintering treatment is 5℃ / min~8℃ / min. Further, the temperature of the pre-sintering treatment can be but not limited to 800℃, 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃, 880℃, 890℃ or 900℃, the time of the pre-sintering treatment can be but not limited to 2h, 2.5h or 3h, and the heating rate of the pre-sintering treatment can be but not limited to 5℃ / min, 6℃ / min, 7℃ / min or 8℃ / min.
[0035] S20, granulating the pre-calcined powder obtained in step S10, and then pressing and molding to obtain a ceramic green sheet.
[0036] In a feasible implementation, before granulating the pre-calcined powder, the following steps are also included: ball milling the pre-calcined powder at a speed of 250 r / min to 300 r / min for 16 h to 20 h. Specifically, the pre-calcined powder is placed in an agate grinding mortar and ground manually with an agate rod, and then placed in a ball mill containing an alcohol medium for secondary ball milling.
[0037] In a feasible implementation, the granulation operation is: the pre-calcined powder is mixed with a binder evenly, and then passed through a 100-mesh screen; wherein the binder has a mass percentage of 5% to 7%. The binder can be, but is not limited to, a 5wt.% polyvinyl alcohol (PVA) solution.
[0038] Furthermore, the operation of compression molding may be, but is not limited to, pressing the embryo into a disc-shaped embryo with a diameter of 13 mm and a thickness of 1 mm at a pressure of 200 MPa.
[0039] S30, performing a debinding process and a sintering process on the ceramic green sheet obtained in step S20 to obtain lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramics.
[0040] In a feasible implementation, the temperature of the debinding treatment is 600°C to 700°C, the holding time of the debinding treatment is 5h to 6h, and the heating rate is 1°C / min to 3°C / min. It is used to remove the adhesive added during granulation. Further, the temperature of the debinding treatment can be but not limited to 600°C, 650°C or 700°C, the holding time of the debinding treatment can be but not limited to 5h, 5.5h or 6h, and the heating rate can be but not limited to 1°C / min, 2°C / min or 3°C / min.
[0041] In a feasible implementation, the sintering temperature is 1150°C to 1200°C, the holding time is 2h to 3h, and the heating rate is 5°C / min to 8°C / min. During sintering, the same component powders are buried in an alumina crucible. Further, the sintering temperature may be, but not limited to, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C or 1200°C, the holding time may be, but not limited to, 2h, 2.5h or 3h, and the heating rate may be, but not limited to, 5°C / min, 6°C / min, 7°C / min or 8°C / min.
[0042] In a feasible implementation, the sintering process also includes the steps of silver coating and polarization. The silver coating operation is as follows: grind and polish the surface of the sintered ceramic sheet, apply silver paste on the upper and lower surfaces, place it in a muffle furnace, heat it to 700℃~750℃ at a heating rate of 5℃ / min~8℃ / min, keep it warm for 20min~30min, and cool it naturally to room temperature. The polarization operation is as follows: place the silvered sample in silicone oil, apply an electric field of 30kV / cm~35kV / cm, and polarize it for 20min~30min.
[0043] The preparation method of the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramics of the technical solution of the present invention is simple in process. After experimental verification, the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramics prepared by the above preparation method can take into account both high-power performance and temperature stability. On the one hand, it can show good performance under high-power conditions; on the other hand, it can maintain stable piezoelectric performance under high-temperature conditions, and is not prone to thermal runaway problems in the face of high-power and high-temperature environments, and can maintain good performance and reliability; in addition, it also has a wide operating temperature range, can adapt to different temperature environments, and can still maintain stable performance in the face of application scenarios with large temperature changes, thereby improving the flexibility and applicability of the application.
[0044] A piezoelectric device according to one embodiment includes the above-mentioned lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic or the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic prepared by any of the above-mentioned methods for preparing lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramics.
[0045] The piezoelectric device of the technical solution of the present invention includes the above-mentioned lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic. After experimental verification, the lead indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic of the technical solution of the present invention can take into account both high-power performance and temperature stability. On the one hand, it can show good performance under high-power conditions; on the other hand, it can maintain stable piezoelectric performance under high-temperature conditions, and is not prone to thermal runaway problems when facing high-power and high-temperature environments, and can maintain good performance and reliability; in addition, it also has a wide operating temperature range, can adapt to different temperature environments, and can still maintain stable performance in the face of application scenarios with large temperature changes, thereby improving the flexibility and applicability of applications.
[0046] With reference to the above implementation contents, in order to make the technical solution of the present invention more specific, clear and easy to understand, the technical solution of the present invention is now exemplified. However, it should be noted that the contents to be protected by the present invention are not limited to the following embodiments.
[0047] Example 1 (x=0.01)
[0048] Example 1 provides a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic and a preparation method thereof. The chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.01Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.94Pb(Zr 0.48 Ti 0.52 ) 3 , the preparation method comprises the following steps:
[0049] (1) Drying the drugs: First, put the drugs needed for the experiment into an oven at 120℃ and dry them for two hours.
[0050] (2) Ingredients: PbO, TiO 2 、ZrO 2 、MnO 2 、In 2 O 3 , Nb 2 O 5 High-purity chemicals (purity> 99.8%) were used as experimental raw materials. 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.94Pb(Zr0.48 Ti 0.52 ) 3 Weigh the materials and proportion them, specifically weigh 13.7460g PbO powder, 2.4067g TiO 2 Powder, 3.4209g ZrO 2 Powder, 0.0892gMnO 2 Powder, 0.0427g In 2 O 3 Powder and 0.0409g Nb 2 O 5 Powder.
[0051] (3) Ball milling: The mixture is milled in a planetary ball mill for 12 h (at a speed of 250 r / min) using anhydrous ethanol as the ball milling medium to fully crush and mix the raw materials. The mixed slurry is dried in an oven.
[0052] (4) Pre-sintering: The ground powder is placed in a metal mold with a diameter of 30 mm and pressed into blocks using a press. The pre-sintering temperature is set to 900 °C, the heating rate is 5 °C per minute, and the pre-sintering time is 2 h to obtain a pre-sintered powder.
[0053] (5) Secondary ball milling: The pre-calcined powder is placed in an agate grinding mortar and ground manually with an agate rod, and then placed in a ball mill containing an alcohol medium for secondary ball milling. The rotation speed is still maintained at 250 r / min, and the secondary ball milling time is changed to 16 h.
[0054] (6) Granulation and tableting: The pre-calcined powder obtained in step (4) is ball-milled and dried for a second time, 5 wt % polyvinyl alcohol solution is added and ground evenly, passed through a 100 mesh sieve, and pressed into a disc-shaped embryo with a diameter of 13 mm and a thickness of 1 mm at a pressure of 200 MPa.
[0055] (7) Debinding: Heating the temperature to 600°C at a rate of 1°C / min and keeping the temperature for 5 h.
[0056] (8) Sintering: The temperature is raised to 1200°C at a rate of 5°C / min. After two hours of holding, the temperature is lowered to 800°C at a rate of 5°C / min. The mixture is then cooled to room temperature in the furnace. During sintering, the powders of the same components are buried in an alumina crucible and fired.
[0057] (9) Silver coating: The surface of the sintered ceramic sheet was polished, and silver paste was applied on the upper and lower surfaces. The sheet was placed in a muffle furnace and heated to 700°C at a rate of 5°C / min, kept at this temperature for 20 min, and then cooled naturally to room temperature.
[0058] (10) Polarization: The silvered sample was placed in silicone oil and an electric field of 30 kV / cm was applied for polarization for 20 min.
[0059] Example 2 (x=0.03)
[0060] Example 2 provides a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic and a preparation method thereof. The chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.03Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.92Pb(Zr 0.48 Ti 0.52 ) 3 The difference between the preparation method and the preparation method of Example 1 is that the raw material ratio is different. In step (2), 13.7163 g of PbO powder and 2.3505 g of TiO 2 Powder, 3.3409g ZrO 2 Powder, 0.0890g MnO 2 Powder, 0.1278g In 2 O 3 Powder and 0.1224g Nb 2 O 5 Powder.
[0061] Example 3 (x=0.05)
[0062] Example 3 provides a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic and a preparation method thereof. The chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is 0.05Pb(In 1 / 2 Nb 1 / 2 ) 3 -0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.90Pb(Zr 0.48 Ti 0.52 ) 3 The difference between the preparation method and the preparation method of Example 1 is that the raw material ratio is different. In step (2), 13.6867 g of PbO powder and 2.2944 g of TiO 2 Powder, 3.2612g ZrO 2 Powder, 0.0888g MnO 2 Powder, 0.2126g In 2 O 3 Powder and 0.2036g Nb 2 O 5 Powder.
[0063] Comparative Example 1
[0064] This comparative example is a comparative example of Example 1, and provides a piezoelectric ceramic and a preparation method thereof. The chemical formula of the piezoelectric ceramic is 0.05Pb(Mn 1 / 3 Nb 2 / 3 ) 3 -0.95Pb(Zr 0.48 Ti 0.52 ) 3 The difference between the preparation method of Example 1 and that of Example 1 is that the raw materials and the proportions are different. In step (2), 13.7609 g of PbO powder and 2.4350 g of TiO 2 Powder, 3.4610g ZrO 2 Powder, 0.0892g MnO 2 Powder and 0.2729g Nb 2 O 5 Powder.
[0065] Performance Test:
[0066] The electrical properties of the samples obtained in Examples 1 to 3 and Comparative Example 1 were tested after standing at room temperature for 24 hours. The test method is as follows. The test results are shown in Tables 1 and Figures 2-3 shown.
[0067] Test method: The piezoelectric constant d33 is tested by the quasi-static d33 tester, and the electromechanical coupling coefficient kp, mechanical quality factor Qm, dielectric constant εr, and Curie temperature Tc are obtained by the impedance analyzer 4294.
[0068] Table 1 Performance data of piezoelectric ceramics of Examples 1 to 3 and Comparative Example 1
[0069]
[0070] Combining Table 1 and Figure 2 It can be seen that when the PIN content is 0.03, the polarization intensity P value is the highest, and the corresponding piezoelectric constant d33 is also the highest, reaching 436pC / N, and the d33*Qm characterizing the high-power performance also reaches the highest value (>60000). Figure 3 It can be seen from the dielectric temperature spectrum that the temperature (Curie temperature) corresponding to the dielectric peak of the ceramic after the introduction of PIN also exceeds 300° C. The above shows that the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramics of the present invention can take into account both high power performance and temperature stability.
[0071] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic, characterized in that: The chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is: 1 / 2 Nb 1 / 2 )O3-0.05Pb(Mn 1 / 3 Nb 2 / 3 )O3-(0.95-x)Pb(Zr 0.48 Ti 0.52 )O3, wherein 0.01≤x≤0.05, x is the molar ratio.
2. The lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 1, characterized in that: The chemical formula of the lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic is: 1 / 2 Nb 1 / 2 )O3-0.05Pb(Mn 1 / 3 Nb 2 / 3 )O3-(0.95-x)Pb(Zr 0.48 Ti 0.52 )O3, wherein x is 0.01, 0.02, 0.03, 0.04 or 0.
05.
3. A method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramics, characterized in that: The steps include: Based on the chemical formula xPb(In 1 / 2 Nb 1 / 2 )O3-0.05Pb(Mn 1 / 3 Nb 2 / 3 )O3-(0.95-x)Pb(Zr 0.48 Ti 0.52 )O3 stoichiometric ratio, wherein 0.01≤x≤0.05, x is a molar ratio, PbO powder, TiO2 powder, ZrO2 powder, MnO2 powder, In2O3 powder and Nb2O5 powder are uniformly mixed, and pre-sintered after drying to obtain pre-sintered powder after sufficient reaction; Granulating the pre-calcined powder, and then pressing and molding to obtain a ceramic green sheet; as well as The ceramic green sheet is subjected to a debinding process and a sintering process to obtain a lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic.
4. The method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 3, characterized in that: The temperature of the pre-sintering treatment is 800° C. to 900° C., the time of the pre-sintering treatment is 2 h to 3 h, and the heating rate of the pre-sintering treatment is 5° C. / min to 8° C. / min.
5. The method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 3, characterized in that: Before the calcined powder is granulated, the following steps are also included: The pre-calcined powder is ball-milled at a rotation speed of 250 r / min to 300 r / min for 16 h to 20 h.
6. The method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 3, characterized in that: The granulation operation is: the pre-burned powder is mixed with the binder evenly, and then passed through a 100-mesh screen; wherein the mass percentage of the binder is 5% to 7%.
7. The method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 3, characterized in that: The temperature of the debinding treatment is 600° C. to 700° C., the heat preservation time of the debinding treatment is 5 h to 6 h, and the heating rate is 1° C. / min to 3° C. / min.
8. The method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 3, characterized in that: The temperature of the sintering treatment is 1150° C. to 1200° C., the heat preservation time of the sintering treatment is 2 h to 3 h, and the heating rate is 5° C. / min to 8° C. / min.
9. The method for preparing lead indium niobate-lead manganate niobate-lead zirconate titanate piezoelectric ceramic according to claim 3, characterized in that: Silver coating and polarization steps are also included.
10. A piezoelectric device, characterized in that: The lead niobate indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic comprises the lead niobate indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic as claimed in claim 1 or 2, or the lead niobate indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic prepared by the preparation method of the lead niobate indium niobate-lead niobate manganate-lead zirconate titanate piezoelectric ceramic as claimed in any one of claims 3 to 9.
Citation Information
Patent Citations
Potassium-sodium lithium niobate-base lead-free piezoelectric ceramic complex with good temperature stability
CN101935215A
Preparation method of lead magnesio-niobate-lead titanate ceramic
CN102757232A
Lead indium niobate-lead magnesium niobate-lead titanate relaxor ferroelectric textured ceramic with high electrical properties and preparation method and application of textured ceramic
CN104987072A
PIN-PMN-PT single crystal and annealing high-temperature polarization method and application thereof
CN116981333A
Piezoelectric Single Crystal and Piezoelectric Single-Crystal Device and Method for Manufacturing the Same
US20070267947A1
Cited By
Lead manganese antimonate-lead indium niobate-lead zirconate titanate piezoelectric ceramic material and method
CN121609571A
